MODEL PEMBENTUKAN ADVANCED GLYCATION END PRODUCTS (AGES) DAN DEGRADASI TIROSIN AKIBAT REAKSI MAILLARD - Suhartono, Eko; Setiawan, Bambang; Mashuri, Mashuri (Lembaga Penelitian Universitas YARSI, 2005)
Maillard reaction or glycosylation reaction is a reaction between amine group and aldehyde group from glucose to form dicarbonyl compound and Advanced Glycation End Products (AGEs). The formation of AGEs have a role in diabetic complications. This work was conducted study the tyrosine degradation reaction model and the formation of AGEs caused by Maillard reaction. The research design was an experimental study with pre and posttest control group design with followed up posttest in 48 hours to 20 days. Two solutions, A and B were used; solution A was a mixture of BSA 30% + buffer phosphate pH 7 + aquadest, and solution B was BSA 30%+ buffer phosphate pH 7+ aquadest+ glucose. The degradation of tyrosine was measured by its absorbance at l=470 nm and the absorbance of AGEs formation at l=340 nm. Model of AGEs formation in solution A followed the equation of Y=0,0289X ? 0,01847 with correlation coefficient R2=0,9767, where as that in solution B followed equation of Y=0,6552X ? 1,5267 with correlation coefficient R2=0,9463. The tyrosine degradation model in solution A followed equation of Y=-0,1232X + 2,7166 with correlations coefficient R2=0,9175 where as that in solution B followed equation of Y=-0,03552X + 0,7762 with coefficient of correlation R2=0,9175. Negative value was observed in correlation between AGEs absorbance with tyrosine in solution A and B reflecting the formation of AGEs followed by tyrosine degradation